MATERIALS RESEARCH FOUNDATIONS radiation effects in silicon carbide. - Lebedev, A. A. (Materials Research Foundations, 2017)
The book reviews the most interesting, in the author's opinion, publications concerned with radiation defects formed in 6H-, 4H-, and 3C-SiC under irradiation with electrons, neutrons, and some kinds of ions. At the beginning, the SiC electrical parameters making this material promising for application in modern electronics are discussed.